[3H]-RS-15385-197, a selective and high affinity radioligand for alpha 2-adrenoceptors: implications for receptor classification. - MacKinnon, A. C. (1992)
1. RS-15385-197 is the most potent and selective alpha 2-adrenoceptor antagonist available. We have used [3H]-RS-15385-197 to define alpha 2-adrenoceptor subtypes. The binding of [3H]-RS-15385-197 to membranes of rat cerebral cortex, rat neonatal lung and human platelets was reversible, saturable and of high affinity. Saturation experiments indicated that [3H]-RS-15385-197 bound to a single population of sites in all 3 tissues with high affinity (0.08-0.14 nM). The density of sites labelled by [3H]-RS-15385-197 was greater in the cortex (275 fmol mg-1 protein) than in the neonate lung (174 fmol mg-1 protein) and human platelet (170 fmol mg-1 protein). The density of sites labelled with [3H]-RS-15385-197 in the cortex was significantly greater than that labelled with [3H]-yohimbine (121 fmol mg-1 protein). 2. The selective alpha 2-adrenoceptor antagonists, idazoxan, yohimbine, rauwolscine and WY 26703 displaced [3H]-RS-15385-197 binding to rat cerebral cortex in a simple manner with Hill slopes close to unity. The affinities derived for these antagonists against [3H]-RS-15385-197 were similar to the values obtained for the displacement of [3H]-yohimbine indicating the alpha 2-adrenoceptor nature of the binding site. 3. alpha 2A-Adrenoceptor selective compounds, oxymetazoline and BRL 44409, showed high affinity for [3H]-RS-15385-197 binding in the human platelet and lower affinity in the neonate lung, while the alpha 2B-selective compounds, prazosin and imiloxan, showed high affinity for [3H]-RS-15385-197 binding in the neonate lung.(ABSTRACT TRUNCATED AT 250 WORDS)